Konflik Bersenjata dan Kewajiban Negara: Telaah Konsep Dar AlHarb Dalam Syariah dan Hukum Internasional - Pelangi, Intan; Taufiq, M. Shofwan (Muhammadiyah Law Review Journal, 2025)
The concept of Dar al-Harb in classical Islamic jurisprudence represents a normative geopolitical construct rooted in a specific historical context, where the world was divided into the realm of Islam (Dar al-Islam) and the realm of hostility (Dar al-Harb). This classification significantly influenced the legitimacy of warfare and international relations in Islamic legal thought. However, modern global political realities have prompted a critical reassessment of this concept, particularly in relation to the contemporary framework of international law, which emphasizes sovereignty, civilian protection, and the prohibition of aggression. This study aims to explore the classical and contemporary interpretations of Dar al-Harb and to examine the normative intersections and conceptual divergences with the principle of state responsibility under international law. This research adopts a normative juridical approach, employing both comparative legal and conceptual methods. The data sources include secondary legal materials such as classical Islamic texts by scholars like Al-Shaybani, Al-Mawardi, and Ibn Taymiyyah, as well as international legal instruments including the UN Charter, the 1949 Geneva Conventions, and the 1998 Rome Statute. Data were analyzed qualitatively using deductive and inductive reasoning to identify doctrinal differences and potential areas for integration between the two legal systems. The findings reveal that while there are fundamental differences particularly regarding the legal basis of hostility and the authority to legitimize war there are also normative convergences, such as the protection of noncombatants and respect for human dignity. The ethical normative reinterpretation of Dar al-Harb illustrates the potential for Islamic legal values to contribute to the development of a more inclusive and just international humanitarian legal framework